2018
DOI: 10.1126/science.aao2140
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete host immunity favors the evolution of virulence in an emergent pathogen

Abstract: Immune memory evolved to protect hosts from reinfection, but incomplete responses that allow future reinfection may inadvertently select for more-harmful pathogens. We present empirical and modeling evidence that incomplete immunity promotes the evolution of higher virulence in a natural host-pathogen system. We performed sequential infections of house finches with strains of various levels of virulence. Virulent bacterial strains generated stronger host protection against reinfection than less virulent strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 44 publications
8
71
1
Order By: Relevance
“…In addition, because non-resistant birds are immuno-suppressed by M. gallisepticum and so cannot mount a protective immune response [17,34,35], any potential maternal effect would require the prior evolution of genetic resistance. Third, we ensured that all birds used in the experiment were captured within 3 months post-fledging and had no prior exposure to the pathogen, meaning that population differences cannot be explained by secondary responses to infection [12,36] (see STAR Methods). Taken together, our results strongly suggest that house finches have evolved genetic resistance in direct response to the pathogen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, because non-resistant birds are immuno-suppressed by M. gallisepticum and so cannot mount a protective immune response [17,34,35], any potential maternal effect would require the prior evolution of genetic resistance. Third, we ensured that all birds used in the experiment were captured within 3 months post-fledging and had no prior exposure to the pathogen, meaning that population differences cannot be explained by secondary responses to infection [12,36] (see STAR Methods). Taken together, our results strongly suggest that house finches have evolved genetic resistance in direct response to the pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…Most notably, our results suggest that apparent evidence for tolerance is likely to be an artifact of inoculation with an early, non-virulent 1994 isolate: inoculation with later-epidemic isolates are required to generate the differences between ancestral and adapted populations predicted under resistance. Second, it has been recently hypothesized that incomplete immunity against M. gallisepticum protects hosts against secondary infections with low virulence isolates, thereby favoring the evolution of increasing virulence [12]. This hypothesis assumes that the selective consequences of secondary infections are sufficiently high to drive the evolution of pathogen virulence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study found an important role of incomplete immunity driving the selection of higher virulence (Fleming‐Davies et al. ). As noted by Ebert and Bull (), the trade‐off hypothesis reduces the relationship between variables to two dimensions when multiple variables may interact to influence, for example, the relationship between virulence and transmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial result obtained by fitting SIR-type models to data on infectious diseases is the discovery that the non-linear relationships between host density and transmission are often better explained by models that incorporate heterogeneity in transmission [44,[71][72][73][74]. Heterogeneity in transmission has been incorporated in these models by including more than one class of hosts (e.g., by assuming that susceptible or infectious individuals are classed in different groups based on age, behaviour or other phenotypic classes [75,76]), or by assuming that the transmission rate is distributed continuously and incorporating a model parameter representing the variation of this distribution (e.g., in humans [43]; fish [77]; and insects [44]).…”
Section: Modeling Heterogeneity In Transmission In Insect-pathogen Symentioning
confidence: 99%